2016
DOI: 10.18553/jmcp.2016.22.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Patients to Prescription Assistance Programs: Effects on Emergency Department and Hospital Utilization

Abstract: This study was not supported by any outside funding. The authors declare no conflicts of interest. Study design was created by Burley, McPherson, and Daratha. Burley Daratha, Selinger, and Armstrong collected the data, with interpretation performed by Burley, Daratha, and Tuttle, assisted by McPherson. The manuscript was written by Burley, Daratha, and Selinger, with assistance from White, and revised by Burley, White, and Selinger, with assistance from Daratha and Tuttle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Previous studies have demonstrated benefits of reducing medication costs and connecting uninsured patients with medication assistance programs, but many outpatient clinics do not routinely enroll patients in these programs. 17 , 18 , 23 - 26 One review concluded that there is a lack of peer-reviewed literature assessing the impact of medication access on health outcomes. 27…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated benefits of reducing medication costs and connecting uninsured patients with medication assistance programs, but many outpatient clinics do not routinely enroll patients in these programs. 17 , 18 , 23 - 26 One review concluded that there is a lack of peer-reviewed literature assessing the impact of medication access on health outcomes. 27…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies likewise demonstrated that increases in medication adherence can positively affect control of chronic conditions and decrease hospitalizations. 11 , 18 , 26 , 28 The data concerning ED visits is less clear, however, with studies showing that medication nonadherence can lead to ED visits, but a lack of evidence demonstrating that decreasing medication costs is associated with decreased ED visits. 25 , 26 , 29 , 30 One study examined rates of acute care utilization following facilitated patient enrollment in medication assistance programs facilitated by a social worker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses may need to refer patients to prescription assistance programs (PAPS) which offer access to free or reduced-price prescriptions (Asthma and Allergy Foundation of America, 2019). Research has found that emergency room visits and hospital readmissions were reduced among the patients who were assisted (Burley et al, 2016). The criticism of PAPs is that eligibility rules can vary by prescription and by pharmaceutical company making it necessary to apply to several different programs to access all needed prescriptions.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Universal screening for suicide risk in the ED increases detection of risk and is widely accepted in both pediatric and adult settings [39][40][41]. The provision of prescription assistance can help address socioeconomic factors known to increase ED usage [42]. Depression symptom severity correlates with increased barriers to health care access, which contributes to increased rates of ED use [18].…”
Section: Somatic Manifestations Of Depression Can Be Misdiagnosed As mentioning
confidence: 99%